Penerapan Akuntansi untuk Aset Bersejarah pada Makam Bung Karno Blitar - Mashudi,; Fia Rachma, (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2022)
The purpose of this research is to determine the use of historical asset accounting at the Bung Karno Blitar Tomb. Accounting for historical assets (legacy assets) is an accounting topic that is still being disputed, and its definition is still a source of contention among professionals. Bung Karno's burial merits special attention as a tourist attraction in Blitar, not least in terms of accounting and reporting. Methods of qualitative inquiry and phenomenological approaches Because it overlaps with historical, social, and cultural factors, the phenomenological approach is seen to be relevant for this research. The manager of the Bung Karno Tomb in Blitar, the Tourism and Culture Office of Blitar City, did not document the Bung Karno Tomb's historical assets, but simply budget realization and inventory lists. Historical assets, in this example Bung Karno's Tomb, were not disclosed since the worth of this tourist attraction, according to him, should not be quantified in monetary terms. despite the fact that it is merely a catalog of past items with no nominal value.